The co-inoculation of Pseudomonas chlororaphis H1 and Bacillus altitudinis Y1 promoted soybean [Glycine max (L.) Merrill] growth and increased the relative abundance of beneficial microorganisms in rhizosphere and root - Zhang, Wentao; Mao, Guohao; Zhuang, Jiayao; Yang, Hao (Frontiers in Microbiology, 2023)
Currently, plant growth-promoting rhizobacteria (PGPR) microbial inoculants are heavily used in agricultural production among which Pseudomonas sp. and Bacillus sp. are two excellent inoculum strains, which are widely used in plant growth promotion and disease control. However, few studies have been conducted on the combined use of the two bacteria. The aim of this study was to investigate the effects of co-inoculation of these two bacteria on soybean [Glycine max (L.) Merrill] growth and physiological indexes and further study the effect of microbial inoculants on native soil microbial communities and plant endophyte microbiota, especially microorganisms in rhizosphere and root. A pot experiment was conducted, and four treatments were designed: group without any strain inoculant (CK); group inoculated with Pseudomonas sp. H1 inoculant (J); group inoculated with Bacillus sp. Y1 inoculant (Y) and group inoculated with equal volume of Pseudomonas sp. H1 inoculant and Bacillus sp. Y1 inoculant (H). Compared with CK, the three inoculant groups J, Y and H exhibited improved soybean growth and physiological indexes, and group H was the most significant (p < 0.05). In terms of rhizosphere microbial community structure, the relative abundance of native Luteimonas (9.31%) was higher in the H group than in the J (6.07%), Y (3.40%) and CK (5.69%) groups, which has potential value of disease suppression. Besides, compared with bacterial microbial communities of the other three groups in soybean roots, group H increased the abundance of beneficial flora for the contents of Allorhizobium-Neorhizobium-Pararhizobium-Rhizobium, Devosia and Methylobacillus significantly increased (p < 0.05). In conclusion, we found that the compound microbial inoculant composed of Pseudomonas sp. H1 and Bacillus sp. Y1 could effectively promote soybean growth, increase yield and improve the beneficial flora in root and rhizosphere and have certain value for soil improvement.